Symptom Profiles in Psychotic Disorder Not Otherwise Specified - Widing, Line; Simonsen, Carmen; Flaaten, Camilla B.; Haatveit, Beathe; Vik, Ruth Kristine; Wold, Kristin F.; Åsbø, Gina; Ueland, Torill; Melle, Ingrid (Frontiers in Psychiatry, 2020)
Introduction: Approximately 10% of patients with psychotic disorders receive the diagnosis “Psychotic disorder not otherwise specified” (PNOS). However, there is a lack of knowledge about the clinical presentations captured by this diagnosis in the mental health services. Therefore, we examined the symptom profiles of participants with PNOS compared to participants with bipolar disorder (BD) and schizophrenia spectrum disorder (SZ) diagnoses. Methods: We here included 1221 participants from the Thematically Organized Psychosis-study at Oslo University Hospital; 792 with SZ, 283 with BD and 146 with PNOS, assessed with SCID-I for DSM-IV. The participants with PNOS were categorized into subgroups based on SCID information. The GAF, PANSS, Alcohol Use Disorders Identification Test (AUDIT) and Drug Use Disorders Identification Test (DUDIT) were used to assess function, clinical symptoms and substance use. Results: In the PNOS group, 44% did not meet the criteria for any specific psychotic disorder, 35.5% had contradictory information making a specific diagnosis difficult, and 20.5% had inadequate information to make a specific diagnosis. The most frequent reason for a PNOS diagnosis was difficulty ruling out a substance-induced psychotic disorder (n=41, 28%). Participants with PNOS were younger and more often first-episode than participants with BD and SZ. They were intermediate between BD and SZ for GAF scores (BD>PNOS>SZ) and PANSS scores (BD